A relação entre estilos parentais na alimentação, dificuldades alimentares e aspectos nutricionais de crianças - Fontanezi, Nathalia Moretti [UNIFESP] (2019)
Objectives: To investigate the association between caregiver’s feeding styles, feeding difficulties, nutritional status and food consumption of children, as well as to evaluate the psychometric characteristics of the Brazilian version of the “Questionário de Estilos Parentais na Alimentação” (QEPA). Methods: Cross-sectional study with 468 children from 1 to 6 years and 11 months of age, in the waiting room of a private hospital, in the city of São Paulo. Data were collected during interviwes with mothers: child age and sex, parentes age and level of education, caregiver feeding styles, feeding difficulties, nutritional status and food consumption. To evaluate the psychometric characteristics we used the Cronbach’s alpha and confirmatory factorial analysis with a subsample (n = 190). For tests of association between variables, the Chi-Square (n = 354), and binary logistic regression (n = 257) were used. Statistical analysis considered significance level at 5%. Results: Considering the total sample, the feeding difficulties according to the parent’s perception was 46,1% of children. Mean age of children was 43,9 ± 17,5 months and 51,3% of females. The most frequente parental style was the permissive, followed by responsive, authoritarian and negligent. The questionnaire presented good internal consistency (Cronbach’s alpha total = 0,79) and the confirmatory factorial analysis was adapted to the suggested model (X²/df = 2,21; p < 0,000; RMSEA = 0,07). The presence of feeding difficulties was associated with parental feeding styles X² (3) = 41,208, (p<0,001),as well as feeding difficulties were also associated with nutritional status (X² (1) = 4,750; p = 0,03 OR 0,61; CI 95% 0,39-0,95). Permissive parental style, the child has a higher BMI and high consumption of industrialized food were predictive factors for not recognize their child with feeding difficulties. Conclusion: The results suggest significant associations between the variables and the Brazilian version of questionnaire was validated.